(untitled) - Hawk, Terrance (Ames, Iowa, 1999)
The electronic version of the print reference book. Includes hypertext-linked table of contents and index and a fully functional search engine for quick searches of the entire reference. Index and Contents entries are linked to the text for quick access
Keywords: Veterinary drugs,Veterinary drugs,Veterinary prescription,Laboratory animals; Dosage,Diseases,Chemotherapy